Decreased Information Replacement of Working Memory After Sleep Deprivation: Evidence From an Event-Related Potential Study - Zhang, Liwei; Shao, Yongcong; Liu, Zhongqi; Li, Chenming; Chen, Yuhong; Zhou, Qianxiang (Frontiers in Neuroscience, 2019)
Working memory (WM) components are altered after total sleep deprivation (TSD), both with respect to information replacement and result judgment. However, the electrophysiological mechanisms of WM alterations following sleep restriction remain largely unknown. To identify such mechanisms, event-related potentials were recorded during the n-back WM task, before and after 36 h sleep deprivation. Thirty-one young volunteers participated in this study and performed a two-back WM task with simultaneous electroencephalography (EEG) recording before and after TSD and after 8 h time in bed for recovery (TIBR). Repeated measures analysis of variance revealed that, compared to resting wakefulness, sleep deprivation induced a decrease in the P200 amplitude and induced longer reaction times. ERP-component scalp topographies results indicated that such decrease primarily occurred in the frontal cortex. The N200 and P300 amplitudes also decreased after TSD. Our results suggest that decreased information replacement of WM occurs after 36 h of TSD and that 8 h TIBR after a long period of TSD leads to partial restoration of WM functions. The present findings represent the EEG profile of WM during mental fatigue.